Microsoft programming, the process of making Gantt Chart / Nazri Mohd Ass’ri - Mohd Ass’ri, Nazri (Universiti Teknologi MARA UiTM,Perak, 2022)
Students are indirectly able to experience and understand the real working environment situation. Industrial training can help students gain exposure to professions and applications in their respective fields. Students need to be prepared to face various situations and communicate well so that accurate information can be conveyed and received clearly. As a Civil Engineering student, it is certainly a worthy experience and opportunity for the trainee to be part of this company. The trainee has taken part in few hydrological data analysis and geographical information software such as compute the rainfall threshold and plotting a river cross section.